2004
DOI: 10.1158/0008-5472.can-03-1807
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell-Derived Nitric Oxide Is Involved in the Immune-Rejection of an Immunogenic Murine Lymphoma

Abstract: The roles played by host-derived nitric oxide (NO) in the growth and subsequent immune rejection of a immunogenic murine lymphoma were investigated by growing the tumor in mice in which the gene for either inducible NO synthase (iNOS) or endothelial NOS (eNOS) had been ablated. This showed that NO from tumor-infiltrating host cells had no significant effect on either tumor growth or immune rejection, although measurements of tumor nitrite levels and protein nitration showed that there had been significant NO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
5
21
0
Order By: Relevance
“…NOS are isoenzymes that catalyze the synthesis of nitric oxide (NO), a free radical whose role in tumor biology is still controversial (37). On the one hand, NO can favor tumor growth and development by stimulating angiogenesis (38) and cause immunosuppression (39, 40); on the other hand, NO could play a role in tumor regression through its ability to induce apoptosis (41) and facilitate an immune response/rejection of the tumor (42). Studies have showed that certain antioxidants in vegetables and fruits regulate NOS expression and NO production.…”
Section: Discussionmentioning
confidence: 99%
“…NOS are isoenzymes that catalyze the synthesis of nitric oxide (NO), a free radical whose role in tumor biology is still controversial (37). On the one hand, NO can favor tumor growth and development by stimulating angiogenesis (38) and cause immunosuppression (39, 40); on the other hand, NO could play a role in tumor regression through its ability to induce apoptosis (41) and facilitate an immune response/rejection of the tumor (42). Studies have showed that certain antioxidants in vegetables and fruits regulate NOS expression and NO production.…”
Section: Discussionmentioning
confidence: 99%
“…NO plays many different biological roles including stimulation of cell growth, apoptosis, and angiogenesis, and inhibits blood clotting (22,(35)(36)(37)). Brindle's group (38) recently reported that tumor-derived NO was an important mechanism for rejection of their EG7 cell line, and that other reactive oxygen species including peroxynitrite can be generated and might be involved. Our EG7 cell line does not produce NO in the presence of 1000 U of IFN-␥ and 25 ng of TNF-␣ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, NO also has stimulatory and inhibitory roles in anti-tumor immunity29. Inhibiting NOS delayed immune rejection of tumors30, and stromal cell production of NO suppressed growth31. Therefore, general inhibition of NOS may not be an effective strategy to control tumor growth.…”
Section: Angiogenic Factors Stimulate No Synthesismentioning
confidence: 99%